IOT Based Progressive Anti Theft ATM Security System. Issue 4 (December 2020) - Ramyasri, S.; Mahalakshmi, M.
Abstract: Automated Teller Machines ATMs are used with one type of approach, usually with cash withdrawals. ATM customers use a lot of ATM facilities and make billions of transactions. In the meantime, Due to inadequate of security, the thefts in the ATMs are also disproportionate. The main objective of our analysis is to minimise the number of ATM robberies. N of this assignment, we use the camera to recognise the face. The IR will activate, the buzzer will warn the sound, and the corresponding alert message will be sent to the assigned user if any of the sensors including temperature. In addition, if someone wants to open the money locker, the gas is sprayed on the robber to make him unconscious. This is why a low-value portable Integrated database server primarily based on the ARM11 computer and the Raspberry Pi operating gadget for Linux needs to be put into operation. This configuration is suggested for ATM safety, consisting specifically of door lock modules, internet, sensors and a face-recognition camera. Whenever theft occurs, an infrared sensor is used here that detects the vibration and temperature of the ATM system and takes critical motion. This machine uses the ARM11 controller to process real-time information acquired using the IR sensor, based primarily on the built-in gadget. The details are communicated to the entire master device based on ARM11 until the IR is detected. The DC engine would then be used to shut down the Automated teller machine lock, the circuit will be used to release fuel inside the ATM to deliver the robber to the unconscious point, the GSM modem will send signals to the local police station and the approved person concerned, and the alarm will eventually come from the buzzer. This can deter the robbery, and the man or woman who is involved in the robbery will be without difficulties.